Supremacy of Law in Malaysia - Paduka Seri Sultan Azlan Muhibbudin Shah, Duli Yang Maha Mulia Sultan Perak (Journal of Malaysian and Comparative Law, 1984)
In the past decade, we have seen in high places being convicted of criminal offences under our law. These people thought they could flout the law with impunity. They were mistaken.